Impacts of Professionalization and Wellbeing Policies on Scottish Prison Workers - Fletcher, Andrew; McKie, Linda; MacPherson, Isobel; Tombs, Jackie (Frontiers in Sociology, 2021)
Prison workers occupy a niche role. Balancing the care and welfare of prisoners while simultaneously restricting their freedoms is a stressful job, laced with danger, that occurs entirely within the bounded context of the prison. Here, wellbeing and professionalism are closely linked and articulated through a range of policies. This article explores the perceptions and experiences of staff in relation to a range of wellbeing and training policies in the Scottish Prison Service (SPS). We interviewed 10 SPS employees, some working directly with prisoners and others in more centralised policy development and support roles. Thematic analysis found a high degree of contentment with such policies but highlighted tensions between their implementation and specific challenges of the prison context. Emerging themes included: supporting wellbeing within the complex dynamic of the prison world; addressing inherent tensions borne out of the underlying threat of violence; and the impact of professionalization. We conclude that while the prison service aspires to offer employees wellbeing and professionalization opportunities similar to those in other sectors, there is a need for such policies to more clearly reflect the unique context of prison work. This might involve co-design of policies and more careful consideration of the pressures, tensions and idiosyncrasies of that rarefied environment.